2023
DOI: 10.1027/2698-1866/a000033
|View full text |Cite
|
Sign up to set email alerts
|

The Green-Eyed Monster in Social Media – Development and Validation of a Digital Jealousy Scale

Abstract: Romantic jealousy describes a feeling when individuals suspect losing their romantic partner to a potential rival. Social media has a high potential to trigger romantic jealousy as it offers almost unlimited opportunities to build social relationships. Thus, it is unsurprising that many studies are now examining social media‐induced jealousy (SoMJ). However, there has been a lack of standardized instruments that can capture SoMJ independently of a specific social media platform. In the present two studies, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Discriminant validity was established with the HEXACO model of personality. Social media friendship jealousy was unrelated to extraversion and weakly associated with agreeableness consistent with previous research on friendship jealousy ( Kokkinos et al, 2020 ) and romantic jealousy ( Gubler et al, 2023 ; Richter et al, 2022 ). Contrary to predictions, social media friendship jealousy had a modest negative association with conscientiousness.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Discriminant validity was established with the HEXACO model of personality. Social media friendship jealousy was unrelated to extraversion and weakly associated with agreeableness consistent with previous research on friendship jealousy ( Kokkinos et al, 2020 ) and romantic jealousy ( Gubler et al, 2023 ; Richter et al, 2022 ). Contrary to predictions, social media friendship jealousy had a modest negative association with conscientiousness.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, low conscientiousness might equate to less reciprocation online, which in turn, generates increased feelings of jealousy. This would help to make sense of some of the discrepant findings in previous research (e.g., Gubler et al, 2023 ; Kokkinos et al, 2020 ). Social media friendship jealousy is also technologically driven via applications, and previous work has shown that conscientiousness negatively predicts social media addiction ( Dailey et al, 2020 ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations